2018
DOI: 10.1186/s12863-018-0628-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic etiologies of the electrical status epilepticus during slow wave sleep: systematic review

Abstract: BackgroundElectrical status epilepticus during slow-wave sleep (ESESS) which is also known as continuous spike-wave of slow sleep (CSWSS) is type of electroencephalographic (EEG) pattern which is seen in ESESS/CSWSS/epilepsy aphasia spectrum. This EEG pattern can occur alone or with other syndromes. Its etiology is not clear, however, brain malformations, immune disorders, and genetic etiologies are suspected to contribute. We aimed to perform a systematic review of all genetic etiologies which have been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 56 publications
7
39
1
3
Order By: Relevance
“…We found that there is a significantly higher rate of congenital heart defects in 3q29Del as compared to 3q29Dup (24.8% vs. 6.5%, p = 0.047), which is in line with previously published studies of 3q29Del and 3q29Dup. We also found a higher rate of 3q29Dup participants reporting seizures as compared to 3q29Del participants (25.8% vs. 15.4%, p = 0.276); while this difference is not statistically significant, it lends additional support to the association between 3q29Dup and seizure phenotypes previously described in case reports (Fernández-Jaén et al, 2014;Kessi et al, 2018;Lesca et al, 2012;Tassano et al, 2018). The registry asks only about the presence or absence of seizures; collecting more data about seizure phenotypes associated with the 3q29 duplication is an important future direction for this work.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We found that there is a significantly higher rate of congenital heart defects in 3q29Del as compared to 3q29Dup (24.8% vs. 6.5%, p = 0.047), which is in line with previously published studies of 3q29Del and 3q29Dup. We also found a higher rate of 3q29Dup participants reporting seizures as compared to 3q29Del participants (25.8% vs. 15.4%, p = 0.276); while this difference is not statistically significant, it lends additional support to the association between 3q29Dup and seizure phenotypes previously described in case reports (Fernández-Jaén et al, 2014;Kessi et al, 2018;Lesca et al, 2012;Tassano et al, 2018). The registry asks only about the presence or absence of seizures; collecting more data about seizure phenotypes associated with the 3q29 duplication is an important future direction for this work.…”
Section: Discussionsupporting
confidence: 81%
“…We also find that seizures, frequently described in case reports of 3q29 duplication syndrome (Fernández-Jaén et al, 2014;Kessi et al, 2018;Lesca et al, 2012;Tassano et al, 2018), are reported in 25% of our study subjects, thus individuals with 3q29 duplication syndrome should be evaluated by a pediatric neurologist. We find feeding problems and chronic constipation are reliably manifest, such that a pediatric gastroenterologist should administer an evaluation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Case reports of 3q29dup report a range of associated characteristics, including developmental delay, speech delay, intellectual disability (ID), ocular and cardiac anomalies, microcephaly, dental anomalies, obesity, and seizures (Aleixandre Blanquer et al, ; Ballif et al, ; Fernández‐Jaén et al, ; Goobie et al, ; Kessi et al, ; Lesca et al, ; Lisi et al, ; Schilter et al, ; Tassano et al, ; Vitale et al, ). Additionally, some case reports have described a disruptive behavioral profile (Quintela et al, ) and behavioral similarities to autism spectrum disorder (ASD) (Lesca et al, ), and one case report identifies an individual with spina bifida (Lawrence, Arreola, Cools, Elton, & Wood, ).…”
Section: Introductionmentioning
confidence: 99%